Meropenem for treating KPC-producing Klebsiella pneumoniae bloodstream infections: Should we get to the PK/PD root of the paradox?. Issue 1 (2nd January 2017) - Del Bono, Valerio; Giacobbe, Daniele Roberto; Marchese, Anna; Parisini, Andrea; Fucile, Carmen; Coppo, Erika; Marini, Valeria; Arena, Antonio; Molin, Alexandre; Martelli, Antonietta; Gratarola, Angelo; Viscoli, Claudio; et al.
ABSTRACT: The objective of this study was to assess the achievement of pharmacokinetic/pharmacodynamic (PK/PD) targets of meropenem (MEM) in critically-ill patients with bloodstream infections (BSI) due to Klebsiella pneumoniae -carbapenemase-producing Klebsiella pneumoniae (KPC-Kp) with MEM minimum inhibitory concentrations (MICs) ≥16 mg/L. Nineteen critically-ill patients with KPC-Kp BSI were given combination therapy including MEM, tigecycline, plus colistin or gentamicin (according to susceptibility testing). MEM was administered as an extended 3-hour infusion of 2 g every 8 hours, or adjusted according to renal function. MEM plasma concentrations were determined by high-performance liquid chromatography. PK/PD targets for MEM were defined as T > 40% 1×MIC and T > 40% 4×MIC. Possible synergisms between MEM and coadministered agents were assessed by time-kill assays based on plasma levels for MEM and on fixed plasma concentrations for the other agents. In none of 19 patients MEM reached any PK/PD target. The actual MEM MICs were 256, 512, and 1024 mg/L in 1, 3, and 15 isolates, respectively. However, theoretically, the PK/PD target of T > 40% 1×MIC could have been achieved in 95%, 68%, 32% and 0% of the isolates for MIC equal to 8, 16, 32, and 64 mg/L, respectively. No synergisms were observed between MEM and coadministered agents. In conclusion, high-dose MEM failed to reach PK/PD targets in 19 patients with BSI due to KPC-Kp with very high MEM MICs. On a theoretical basis, our results suggest a possible usefulness of MEM against resistant blood isolates with MICs up to 32 mg/L.